Is Age a Determinant Factor in EVAR as a Predictor of Outcomes or in the Selection Procedure? Our Experience - Machado,Rui (2016)
Abstract Introduction: Endovascular aneurysm repair (EVAR) is the therapy of choice in high risk patients with abdominal aortic aneurysm. The good results described are leading to the broadening of clinical indications to younger patients. However, reintervention rates seem higher and even with successful treatment sometimes there is growth of the aneurysm sac and rupture, meaning a failure of the therapeutic goal. This study proposes to analyse the impact of age in patients' selection and post-EVAR results. Methods: The clinical records of consecutive patients undergoing endovascular aneurysm repair, between 2001 and 2013, were retrospectively reviewed. Patients were divided according to age groups (<70, 70-80 and >80 years). Gender, body mass index, aneurysm anatomic features, neck characteristics, iliac morphology, surgical indication, endograft type, anesthesic risk classification, length of stay, reinterventions and mortality were analysed and compared. Results: The study included 171 patients, 161 (94.1%) men, and mean age 74.1±8.9 years. The age group under 70 had 32% of the patients. Only three characteristics were found different among age groups: 1) body mass index was higher in younger patients, with a considerable trend toward significance (P=0.06); 2) surgical indication, in the younger group, surgeon's and the patient's option were more proeminent (P<0.05); 3) erectile dysfunction was higher in elderly group (P<0.05). No other clinical and anatomical characteristics or final outcomes were found statisticaly different among age groups. Conclusion: The absence of statistically differences in mortality and reinterventions among age groups suggests that age by itself is not a relevant factor in endovascular aneurysm repair. Indeed, the three characteristics different in younger (obesity, sexual function and patient's choice) favor endovascular aneurysm repair.